Chicken soup for the soul think positive : 101 inspirational stories about counting your blessings and having a positive attitude - Canfield, Jack 1944-; Hansen, Mark Victor; Newmark, Amy (Chicken Soup for the Soul Publishing, 2010)
A collection of 101 true personal stories from regular people about the power of positive thinking in their lives and how they use positive thinking, count their blessings, and are grateful.